2011
DOI: 10.1088/0268-1242/26/4/045015
|View full text |Cite
|
Sign up to set email alerts
|

Lateral epitaxial overgrowth of GaN on a patterned GaN-on-silicon substrate by molecular beam epitaxy

Abstract: We report here the lateral epitaxial overgrowth (LEO) of GaN on a patterned GaN-on-silicon substrate by molecular beam epitaxy (MBE) growth with radio frequency nitrogen plasma as a gas source. Two kinds of GaN nanostructures are defined by electron beam lithography and realized on a GaN substrate by fast atom beam etching. The epitaxial growth of GaN by MBE is performed on the prepared GaN template, and the selective growth of GaN takes place with the assistance of GaN nanostructures. The LEO of GaN produces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Most notably, SAG allows the reduction of threading dislocations at the grown surface by trapping and bending with lateral overgrowth 5 7 8 9 10 11 12 and it allows accommodation of thermal stresses during heteroepitaxial growth 13 14 . The SAG of arsenide and phosphide III-V materials has been analyzed quite extensively but less studies were reported for nitride materials except for nano-scale mask openings and spacings 6 7 9 15 16 17 18 19 20 21 . The interest in submillimeter scale heteroepitaxy and SAG have witnessed recently increased interest for large scale integration of light emitting diodes (LEDs) 22 23 24 and the development of high power devices 25 26 27 28 29 30 31 .…”
mentioning
confidence: 99%
“…Most notably, SAG allows the reduction of threading dislocations at the grown surface by trapping and bending with lateral overgrowth 5 7 8 9 10 11 12 and it allows accommodation of thermal stresses during heteroepitaxial growth 13 14 . The SAG of arsenide and phosphide III-V materials has been analyzed quite extensively but less studies were reported for nitride materials except for nano-scale mask openings and spacings 6 7 9 15 16 17 18 19 20 21 . The interest in submillimeter scale heteroepitaxy and SAG have witnessed recently increased interest for large scale integration of light emitting diodes (LEDs) 22 23 24 and the development of high power devices 25 26 27 28 29 30 31 .…”
mentioning
confidence: 99%
“…These results demonstrate the potential of this pillar array template for GaN-based devices and freestanding substrates. Yongjin Wang have demonstrated the LEO of GaN on a patterned GaN-on-silicon substrate by MBE [35]. The epitaxial growth of GaN is performed on the prepared GaN template, and the selective growth of GaN takes place with the assistance of GaN nanostructures.…”
Section: Materials Of Iii-nitride Grown On Si (111)mentioning
confidence: 99%
“…Among the approaches towards creating suspended III-nitride structures, growth of III-nitride on freestanding structured template is an emerging technology. During growth process, nanoscale structures locally change the growth conditions and thus, the selective growth can be achieved to generate epitaxial III-nitride structures with smooth facets [ 8 - 11 ]. Meanwhile, freestanding III-nitride structures are formed by growth method and free of the etching damage.…”
Section: Introductionmentioning
confidence: 99%